Microwave-assisted solvothermal synthesis of cubic ferrite (MFe2O4, M = Mn, Zn, Cu and Ni) nanocrystals and their magnetic properties - A. Phuruangrat (2018)
© 2018, Inst Materials Physics. All rights reserved. MFe2O4(M = Mn, Zn, Cu and Ni) nanoparticles were synthesized by a microwave-assisted solvothermal method. The as-synthesized MFe2O4nanoparticles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy and transmission electron microscopy. The magnetic properties were examined by vibrating sample magnetometer (VSM). XRD patterns show cubic ferrite MFe2O4(M = Mn, Zn, Cu and Ni) with a spinel-type structure. FTIR spectra show the vibration band at ~600–585 cm−1of stretching mode of Fe–O and at ~407–406 cm−1of stretching mode of M–O. The VSM analysis revealed ferromagnetic hysteresis in the field range of ±1000 Oe and ±3000 Oe for the NiFe2O4and MnFe2O4samples, respectively, whereas the superparamagnetic behavior for the ZnFe2O4and CuFe2O4samples.